PENINGKATAN KEMAMPUAN MEMAHAMI TEKS ANEKDOT DENGAN METODE PEMBELAJARAN PENEMUAN SISWA KELAS X MIPA 2 SMAN 3 KOTA BENGKULU - Kencana, Lia (UNIB Press, 2016)
The purpose of study was to determine the ability in comprehending anecdote text through discovery learning method. The subject of this research is the students grade X MIPA 2 SMAN 3 Bengkulu city academic tear 2015/2016. Kind of the research is classroom action research. The data of this research is the ability in comprehending anecdote text and students and teacher’s abservation sheet. Based on the research that discovery learning can increase ability in comprehending anecdote text for the students grade X MIPA 2 SMAN 3 Bengkulu City. The result can be seen in score action research cycle I with the average score 70,42 it is good category and in action research cycle II 80,85 it is the best category. The classical learning achievement in cycle I 48,39% and in cycle II 87,05%, it means that there is significant increase between cycle I and cycle II.